Ali regulacija in kritje cen zdravil vplivata na javne izdatke za zdravila? - Kajdiž, Romana (Zdravniški vestnik, 2012)
Background: Slovenia aims to regulate and reimburse prices of medicinal products in order to manage and reduce public expenditure for medicinal products. Two levels of reference prices (R) are used: external R with a regulated maximum price and internal R with a maximum attributed value, defined by reference pricing for interchangeable medicinal products. The Health Insurance Institute of Slovenia covers expenses for their prescribed use and negotiates prices. The objective of our article was to confirm the basic thesis that the price regulation system and reimbursement have caused the decline in the regulated and reimbursed wholesale prices for medicinal products. Consequently, the decline in prices might contribute to a reduction of public expenditures for medicinal products. Methods: The research covered 760 regulated and reimbursed wholesale prices for both groups of medicinal products prescribed on an outpatient prescription and financed by public expenditures. The Laspeyres index and Wilcoxon signed ranks test are used to estimate the impact of wholesale price regulation system and reimbursement on the trends in nominal and real wholesale prices of medicinal products in the period 2003-2010. Results: The main thesis that the nominal and real wholesaleprices of medicinal products declined during the years 2003-2010, wasconfirmed by the Laspeyres index. The Wilcoxon signed ranks test further confirmed the existence of statistically significant differences in the wholesale prices of medicinal products (p < 0.05). With 5 % significance level, we can conclude that the regulated and reimbursed nominal and real wholesale prices of medicinal products have declined during the analysed years. The regulated and reimbursed nominal and real wholesale prices of generic medicinal products have declined more than the prices of original medicinal products.
Keywords: cene zdravil; določanje cen medsebojno zamenljivih zdravil z najvišjo priznano vrednostjo; eksterne referenčne cene; external reference price; internal reference prices; interne referenčne cene; kritje cen zdravil; price regulation for medicinal products; prices of medicinal products; reference pricing mutually interchangeable medicinal products with maximum attributed value; regulacija cen zdravil; reimbursement of expenses for medicinal products; Slovenia; Sloveniaj; Slovenija